Environmental consciousness and brand equity: An impact assessment using analytical hierarchy process (AHP). Issue 1 (6th February 2017) - Misra, Siddharth; Panda, Rajeev Kumar
Abstract : Purpose: The purpose of this paper is to investigate the activities of environmental consciousness from socio-psychographic perspectives and hence evaluates its effect on brand equity through intervening elements of environmental attributes (EAt). It further attempts to research the effect of the environmental performance, environmental communication and environmental positioning in enhancing brand equity. Indian refrigeration industry, particularly the air conditioners and refrigerator brands are chosen to convey and receive the research inputs as their impact on environment is easily interpretable. Design/methodology/approach: A hypothesized model comprising the environment consciousness and association dimensions with brand equity is framed. In total, 74 expert respondents from four state capital cities of India participated in the survey and the model has been tested in the scope of analytical hierarchy process (AHP). Findings: The result shows that the EAt and activities can be prioritized and subsequently efficient resource allocation can be done. It also gives theoretical arguments to legitimize the environmental practices. Practical implications: On the other hand, clients have numerous options, and a competitive advantage may not be maintained. Regardless of the fact that clients are environmentally conscious of a given refrigeration brand at the present time that they are utilizing, they may observe that they are much more charmed with a competitors' enhanced environmental dimensions. All methods that take a try at an enhanced brand equity must be continually determined by environmental consciousness. The above can be accomplished if the evaluations of competitors by the clients are known. The AHP-ECBE technique depicted in this study accordingly helps refrigeration organization to devise and keep up a pertinent, focused plan for persistent improvements in environmental dimensions. It offers a "greater image" in brand equity administration. Originality/value: If legitimately done in a generalized way, environmental activities like eco-literacy, interpersonal influence and value orientation can impact EAt and contribute in building brand equity.